GE_GERICHTE C/10749/2011 vom 10. Mai 2013 - GE Cour de justice (2013)
; OBLIGATION D'ENTRETIEN ; ENFANT ; MAJORITÉ(ÂGE) ; FORMATION(EN GÉNÉRAL) ; SUPPRESSION(EN GÉNÉRAL) ; CONCLUSIONS ; DOCUMENT ÉCRIT | CC.277.2 CC.286.2